2014
DOI: 10.1002/psc.2725
|View full text |Cite
|
Sign up to set email alerts
|

Peptide internalization enabled by folding: triple helical cell-penetrating peptides

Abstract: Cell-Penetrating Peptides (CPPs) are known as efficient transporters of molecular cargo across cellular membranes. Their properties make them ideal candidates for in vivo applications. However, challenges in development of effective CPPs still exist: CPPs are often fast degraded by proteases and large concentration of CPPs required for cargo transporting can cause cytotoxicity. It was previously shown that restricting peptide flexibility can improve peptide stability against enzymatic degradation and limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…CMP-modification has been demonstrated to not only enhance vector availability/stability in the delivery site, but also to provide a ligand promoting cellular uptake through endocytic pathways linked to high efficiency expression. Additional studies have demonstrated that the CMPs’ unique triple helical structure is integral in achieving enhanced cellular binding and cell penetration [78]. For instance, CMPs were successfully used to enhance liposome targeting of melanoma cells through specific ligand/receptor interactions, whereas no binding to non- targeted cells was recorded [79].…”
Section: Discussionmentioning
confidence: 99%
“…CMP-modification has been demonstrated to not only enhance vector availability/stability in the delivery site, but also to provide a ligand promoting cellular uptake through endocytic pathways linked to high efficiency expression. Additional studies have demonstrated that the CMPs’ unique triple helical structure is integral in achieving enhanced cellular binding and cell penetration [78]. For instance, CMPs were successfully used to enhance liposome targeting of melanoma cells through specific ligand/receptor interactions, whereas no binding to non- targeted cells was recorded [79].…”
Section: Discussionmentioning
confidence: 99%
“…29 Lowering the temperature from physiological value affects not only peptide folding, but also the effectiveness of nanocarrier cellular uptake due to changes induced in the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…For all conditions, the fluorescence signal is observed within cell cytoplasm, as previously shown for tagged peptides that carry an RRGRRG sequence in the CPP domain. 29 If the desired location of peptide carrier is nucleus, the CPP domain can be altered to R 6 , what causes accumulation of peptide in the nuclear bodies that contain high concentration of nucleic acids. 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11) Herein, we report the strategy for conjugating the CPP to IgG, properties of the complexes, and its delivery and intracellular localization.…”
Section: )mentioning
confidence: 99%